Production of wax esters - Basri, Mahiran; Gunawan, Erin Ryantin; Abdul Rahman, Mohd Basyaruddin; Salleh, Abu Bakar; Raja Abdul Rahman, Raja Noor Zaliha (2011)
Wax ester are prepared by reacting a solution of palm oil in an organic solvent with oleyl alcohol in the presence of an immobilized lipase wherein molar ratio of palm oil to oleyl alcohol is between 1:2 and 1:4. Immobilized lipase used is present in an amount which is equivalent to not less that 1000 ug of protein per milli-mole of palm oil used and the reaction is carried out at 40 ⁰C to 50 ⁰C for a period of not less that 5 hours. The organic solvent used has a value of log P not less than 3.5.